Time, experience and belief - Skokowski, P (Brill, 2023)
A model is proposed for human-like information-gathering and -utilizing systems. This model uses sensory experience, and subsequent processed belief contents, to provide a notion of psychological time for these agents. This model shows how a narrative can be formed to provide concepts of a ‘now’, a ‘past’, a ‘future’, and perhaps even a ‘flow’ for psychological time. The proposal is that conscious, occurrent access at any moment to registers with different kinds of contents warrants beliefs about relations in time, while recognizing differences between interpretations of psychological time and time as understood in physical theories.